2006
DOI: 10.1002/pri.327
|View full text |Cite
|
Sign up to set email alerts
|

Balance and gait improved in patients with MS after physiotherapy based on the Bobath concept

Abstract: The findings indicate that balance and gait can be improved after physiotherapy based on the Bobath concept, but this should be further evaluated in larger controlled trials of patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 166 publications
(257 reference statements)
1
38
0
Order By: Relevance
“…As a result, new approaches are demanded. In recent literature, physiotherapy based on the Bobath concept has been used to improve functions in MS patients [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, new approaches are demanded. In recent literature, physiotherapy based on the Bobath concept has been used to improve functions in MS patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Bobath-based exercises have recently been recommended for use in MS rehabilitation [14]. According to the Bobath concept, the trunk has a key role in functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[64] It has been demonstrated that human action execution (i.e., to make a cup of coffee) required three main phases: motor planning, motor execution, and movement control. [62] It is necessary in patients with SM to stimulate feedback and feed forward mechanisms and sensorimotor integration especially during the motion control phase [65].…”
Section: Discussionmentioning
confidence: 99%
“…As such, core strengthening in various forms has been the subject of intervention [16][17][18][39][40]. Although these studies generally have limitations in design and have used different approaches and outcomes, together they show an overall positive effect on gait and mobility outcomes.…”
Section: Discussionmentioning
confidence: 99%